2018
DOI: 10.3390/met8070546
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Recycle Stainless–Steel Duplex UNS S31803 Chips

Abstract: Due to the increased consumption of raw materials, energy, and the waste it generates, recycling has become very important and fundamental for the environment and the industrial sector. The production of duplex stainless-steel powders with the addition of vanadium carbide in the high energy mechanical milling process is a new method for recycling materials for the manufacture of components in the industrial sector. This study aims to reuse the chips from the duplex stainless-steel UNS S31803 by powder metallur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Metal chips can be recycled by turning them into powders by using processes like milling, gas atomization, and electrolytic decomposition. A high-end ball milling process using vanadium carbides has been studied by Mendonça et al [281][282][283] for recycling stainless steel chips (Figure 26).…”
Section: Powder Metallurgy (Pm)mentioning
confidence: 99%
“…Metal chips can be recycled by turning them into powders by using processes like milling, gas atomization, and electrolytic decomposition. A high-end ball milling process using vanadium carbides has been studied by Mendonça et al [281][282][283] for recycling stainless steel chips (Figure 26).…”
Section: Powder Metallurgy (Pm)mentioning
confidence: 99%
“…This study also demonstrated that increasing the reinforcing concentration results in a decrease in average particle size. In contrast, another study demonstrated that the sintered composite has a lower hardness than the as-received alloy and that the porosity of the sintered composite is to blame for the failure [ 169 ].…”
Section: Ball Millingmentioning
confidence: 99%
“…This study also presented that: the increase in the reinforcement concentration results in the reduction of average particle size. However, a similar study shows that the hardness of the sintered composite was smaller than the as-received alloy, and the failure was attributed to the porosity of sintered composite [ 37 ]. Other researchers also exhibited a significant effect on the fragmentation of particles in the presence of reinforcements, d = 80 µm in Ti 6 Al 4 V powder and 4 µm in Ti 6 Al 4 V-10 wt.% nanoalumina [ 27 ].…”
Section: Recycling Chips For Powder Metallurgy Applicationsmentioning
confidence: 99%